Effect of single doses of IV palonosetron, up to 2.25 mg, on the QTc interval duration: a double-blind, randomized, parallel group study in healthy volunteers - Morganroth, Joel; Flaharty, Kristen K.; Parisi, Simona; Moresino, Cecilia (Supportive care in cancer, 2016)
Purpose The use of serotonin type 3 (5-HT 3 ) receptor antagonists (RAs) in the prevention of nausea and vomiting caused by emetogenic chemotherapy is part of a comprehensive management strategy for patients undergoing chemotherapy. Electrocardiographic effects have been reported in patients after intravenous administration of 5-HT 3 RAs. The present study investigated the electrocardiogram (ECG) profile of the 5-HT 3 RA palonosetron following International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) E14 Guidelines. Methods A total of 221 healthy subjects (101 females, 120 males) were randomized in this phase I, double-blind, double-dummy, parallel group study and assigned to one of five treatments: placebo, palonosetron (0.25, 0.75, or 2.25 mg), or moxifloxacin (400 mg). ECGs were recorded for 24 h pre-dosing until 48 h post-dose. The primary endpoint was the placebo time-matched and baseline-subtracted individual QTc interval prolongation (ΔΔQTcI). Results The QTc interval was not prolonged after administration of palonosetron (ΔΔQTcI upper confidence interval was <10 ms for all time points in all palonosetron treatment groups). Assay sensitivity was confirmed with the expected change in the QTc interval after administration of the positive control moxifloxacin. Conclusions Palonosetron, even at supratherapeutic doses, has no effect on cardiac repolarization as measured by the QTc interval in a validated controlled clinical trial.